2013
DOI: 10.1590/s1517-83822013005000034
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Paratuberculosis and the microelements Copper, Zinc, Iron, Selenium and Molybdenum in Beef Cattle

Abstract: To study the deficiency of minerals and its relationship with Paratuberculosis, blood, serum, and fecal samples were obtained from 75 adult bovines without clinical symptoms of the disease and from two bovines with clinical symptoms of the disease, from two beef herds with a previous history of Paratuberculosis in the Province of Buenos Aires, Argentina. Serum samples were processed by ELISA and feces were cultured in Herrolds medium. Copper, zinc and iron in serum were quantified by spectrophotometry and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…CAT and SOD are the main antioxidant enzymes of the oxidation resistance defense system in fish [14]. GSH-PX is an enzyme that prevents damage to cellular membranes and participates in the immune response of animals, which can directly reflect the body's antioxidant capacity and immune level [15]. Thus, these indicators can be used to show the immune ability of fish and increase of the immune enzyme activity can enhance the immune system of fish.…”
Section: Introductionmentioning
confidence: 99%
“…CAT and SOD are the main antioxidant enzymes of the oxidation resistance defense system in fish [14]. GSH-PX is an enzyme that prevents damage to cellular membranes and participates in the immune response of animals, which can directly reflect the body's antioxidant capacity and immune level [15]. Thus, these indicators can be used to show the immune ability of fish and increase of the immune enzyme activity can enhance the immune system of fish.…”
Section: Introductionmentioning
confidence: 99%
“…In bovines, CD14 + CD16 − is defined as the M1 classical subset, the M2 non-classical subset is CD14 − CD16 ++ , and the intermediate subset is CD14 + CD16 + [ 14 ]. Nutrient and micronutrient status may affect the Th1/Th2 bias, for instance it has been shown that a Copper (Cu) deficiency reduces the ability of cattle to produce IFNγ and TNFα by mononuclear cells [ 15 , 16 ]. In an assessment of function, NO production was also increased [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paolicchi et al (2013) realizaram estudo com amostras de soro bovino e observaram relação entre a deficiência de selênio com a infecção por Map. Os autores também constataram que um aumento de 10ppm de ferro no solo pode estar associado com o aumento no número de animais soropositivos para PTB.…”
Section: Introductionunclassified